MEDIA OF PAIRS CARDS IN INCREASING ECONOMY STUDENTS’ ACTIVENESS AND LEARNING OUTCOMES ON ACCOUNTING MATERIALS FOR SERVICE COMPANIES - Umi Fathonah Rubiyatin; Rahmat Mulyono (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Learning is an interaction between teachers and students that is influenced by various factors, including learning methods, learning strategies, and learning media. The inappropriate use of the methods, strategies, and media will influence the learning objectives, which are not being achieved optimally. The low level of activity and learning outcomes in the Economy for Class XII on Service Company Accounting material at MAN 1 Gunungkidul encouraged researchers to conduct Classroom Action Research (CAR). What was examined in the research was the learning application of applying pairs card question media, increasing students’ activity, and students’ learning outcomes. The method used was observation to determine the learning process and tests of learning outcomes. The research results indicate that there was an increase in students’ activity during the learning process. When applying question card media, at the beginning of high learning activity it was only 5%. In the first cycle, the result increased to 19%. At the end of the second cycle increased to 34.9%. The students’ average value also increased where in the initial conditions, the students who completed was 31%, in cycle 1 the students who completed was 65.5%, while in cycle 2 the students who completed was 80%. Thus, it can be concluded that the use of question card media can increase Economy students’ activeness and learning outcomes on Accounting Materials for Service Companies.